The know-do gap in quality of health for chronic non-communicable diseases in rural China - Meng, Sha; Wang, Qingzhi; Wu, Yuju; Xue, Hao; Li, Linhua; Ye, Ruixue; Chen, Yunwei; Pappas, Lucy; Akhtar, Muizz; Dill, Sarah-Eve; Sylvia, Sean; Zhou, Huan; et al. (Frontiers in Public Health, 2022)
Proper management of non-communicable diseases (NCDs) is a severe challenge to China’s rural health system. This study investigates what influences the poor medical treatment of NCDs (diabetes and angina) by evaluating the “know-do gap” between provider knowledge and practice. To determine whether low levels of provider knowledge low quality of patient care is the primary constraint on the quality of NCDs diagnosis and treatment in rural China. Providers from Village Clinics (VC) and Township Health Centers (THC) and Standardized Patients (SP) were selected by a multi-stage random sampling method. Clinical vignettes were administered to 306 providers from 103 VCs and 50 THCs. SPs presented diabetes symptoms completed 97 interactions with providers in 46 VCs and 51 THCs; SPs presented angina symptoms completed 100 interactions with providers in 50 VCs and 50 THCs. Quality of process, diagnosis and treatment were assessed against national standards for diabetes and angina. Two-tailed T-tests and tests of proportions for continuous outcomes and tests of proportions for binary dependent variables were used to compare vignette and SP results. Differences between vignette and SP data calculated the know-do gap. THC providers demonstrated significantly more knowledge in vignettes and better practices in SP visits than VC providers. However, levels of knowledge were low: 48.2% of THC providers and 28.2% of VC providers diagnosed type 2 diabetes, while 23.8% of THC providers and 14.7% of VC providers diagnosed angina. With SPs, 2.1% of THC providers and 6.8% of VC providers correctly diagnosed type 2 diabetes; 25.5% of THC providers and 12.8% of VC providers correctly diagnosed angina. There were significant know-do gaps in quality of diagnosis process , diagnosis, and treatment for diabetes (p<0.01), and in diagnosis process quality (p<0.05) and treatment quality for angina (p<0.01). Providers display low levels of knowledge when treating diabetes and angina. Despite low knowledge, evidence of the know-do gap indicates that low-quality healthcare is the primary constraint on the quality of NCD diagnosis and treatment. Our research findings provide a new perspective for the evaluation of the medical quality and a technical basis for the development of new standardized cases in the future.